Last Year at Betty and Bob's: An Adventure - Doruff, Sher (Book collections on Project MUSE., 2018)
Last Year at Betty and Bob's: An Adventure is the second in a series of three novellas emerging from a writing practice that taps the cusp of consciousness between dreaming and waking. A storyline, or genealogy, tinted a shade of RGB red, is fashioned by thinking through the felt unthought of this between space -- a fabulation, an anarchive of what passes through. Lucid dreaming of this type is rife with allusions to conceptual and material goings-on, manifesting in awkward imaginaries. The dream personas are rendered as complex character amalgams with nomadic ages, sexes, genders, and phenotypes. Occurrences of lived "fact" elide with a hallucinatory real as speculation. In An Adventure, a feral feminist artist collective, The Bettys, inhabit a timeless Arcades Project. This is their experiment in wild hypo-consumerism. The event of Red Betty's fall generates the advent of a turn. A cleaving. The intra-play of personal politics and activist artistic practices is surreally suffused with attention to color, to life and death, to lightness and heaviness.